Age and ageing: What do they mean?. (30th July 2020) - Räsänen, Joona
Abstract: This article provides a philosophical overview of different approaches to age and ageing. It is often assumed that our age is determined by the amount of time we have been alive. Here, I challenge this belief. I argue that there are at least three plausible, yet unsatisfactory, accounts to age and ageing: the chronological account, the biological account, and the experiential account. I show that all of them fall short of fully determining what it means to age. Addressing these problems, I suggest the Two‐tier principle of age: whenever the three accounts of age contradict, combine the two accounts that differ the least, and reject the third. However, while this principle does solve some difficulties, it is itself vulnerable to problems; therefore I propose we should jettison it. I conclude that there are no accounts to ageing that are satisfactory; they all come with a bullet to bite.